2019
DOI: 10.14515/monitoring.2019.6.07
|View full text |Cite
|
Sign up to set email alerts
|

Может Ли Вовлеченность Студентов Во Внеучебные Мероприятия Способствовать Развитию Мягких Навыков?

Abstract: Такие навыки, как критическое мышление и работа в команде, приобрели особую важность в XXI веке. Они считаются основополагающим условием успеха на рынке труда и важным аспектом учебной программы в университете. Во всем мире педагоги и политики в сфере образования ищут пути развития и совершенствования этих навыков у студентов, например, вовлекая их в различные мероприятия, реализуемые на базе университета. Цель данного исследования — оценить вклад участия студентов во внеучебных мероприятиях в развитии навыков… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…It is possible that the socialisation that occurs when participating in this type of activity has an influence on the social awareness of the individual, as they experience situations of relationships between people, where they can understand how others feel, identify with a social group, etc. In line with these findings is the work of Shcheglova [33], who found that those who participate in extracurricular activities obtain more benefits in interpersonal skills and teamwork than those who do not participate.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is possible that the socialisation that occurs when participating in this type of activity has an influence on the social awareness of the individual, as they experience situations of relationships between people, where they can understand how others feel, identify with a social group, etc. In line with these findings is the work of Shcheglova [33], who found that those who participate in extracurricular activities obtain more benefits in interpersonal skills and teamwork than those who do not participate.…”
Section: Discussionsupporting
confidence: 53%
“…For this reason, in many countries, content has been incorporated into the educational landscape that works especially on these dimensions of the individual. Within this context, there is evidence of studies in both formal [27,28] and non-formal settings [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…University students are demanded to have good communication skills, especially in English, to promote their career employment in the future (Afrianto & Gulö, 2019;Rana, Bashir, & Abbas, 2020;Rido, 2020a). Not only communication skills but the students must also be equipped with critical thinking skills because those are the top skills to enter the job market in the 21st century (NACE, 2020;Rido, 2019;Shcheglova, 2019). University students can acquire communication and critical thinking skills from university lectures through interaction (Saleh, 2019;Ranta & Harmawati, 2017).…”
Section: Introductionmentioning
confidence: 99%